Statin Therapy Reduces the Likelihood of Suboptimal Blood Pressure Control among Ugandan Adult Diabetic Patients - Lumu, William; Kampiire, Leaticia; Akabwai, George Patrick; Kiggundu, Daniel Ssekikubo; Kibirige, Davis (Therapeutics and Clinical Risk Management, 2017)
Hypertension is one of the recognized risk factors of cardiovascular diseases in adult diabetic patients. High prevalence of suboptimal blood pressure (BP) control has been well documented in the majority of studies assessing BP control in diabetic patients in sub-Saharan Africa. In Uganda, there is a dearth of similar studies. This study evaluated the prevalence and correlates of suboptimal BP control in an adult diabetic population in Uganda.
Keywords: Suboptimal blood pressure control; Statin therapy; Diabetic